Influence of planets on debris discs in star clusters: I. The 50 au Jupiter - Wu, Kai; Kouwenhoven, Thijs; Spurzem, Rainer; Pang, Xiaoying (Monthly notices of the Royal Astronomical Society, 2023)
Although debris discs may be common in exoplanet systems, only a few systems are known in which debris discs and planets coexist. Planets and the surrounding stellar population can have a significant impact on debris disc evolution. Here, we study the dynamical evolution of debris structures around stars embedded in star clusters, aiming to determine how the presence of a planet affects the evolution of such structures. We combine NBODY6++GPU and REBOUND to carry out N-body simulations of planetary systems in star clusters ($N=8\, 000$; Rh = 0.78 pc) for a period of 100 Myr, in which 100 solar-type stars are assigned 200 test particles. Simulations are carried out with and without a Jupiter-mass planet at 50 au. We find that the planet destabilizes test particles and speeds up their evolution. The planet expels most particles in nearby and resonant orbits. Remaining test particles tend to retain small inclinations when the planet is present, and fewer test particles obtain retrograde orbits. Most escaping test particles with speeds smaller than the star cluster’s escape speed originate from cold regions of the planetary system or from regions near the planet. We identify three regions within planetary systems in star clusters: (i) the private region of the planet, where few debris particles remain (40-60 au), (ii) the reach of the planet, in which particles are affected by the planet (0-400 au), and (iii) the territory of the planetary system, most particles outside which will eventually escape (0-700 au).
Veröffentlicht: 12. Juni 2023
Gesehen am 28.08.2023